2022
DOI: 10.1371/journal.pone.0279109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise-induced fatigue and heat exposure on soccer-specific decision-making during high-intensity intermittent exercise

Abstract: Global warming and the globalisation of sport has increased the prevalence of sports competitions being held in hot environments. However, there is currently limited research investigating the impact of the heat on soccer-specific decision-making skills during exercise reflective of the physical demands of match-play. Therefore, the effects of heat exposure on physical and soccer-specific decision-making performance, biological markers (i.e., metanephrines), appraisal (i.e., challenge vs. threat) and affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…The results of the present study showed that exposure to heat led to a decrease in anticipation performance in elite female players. Our results mirror those reported by Donnan et al 2 who examined the effects of hot (32°C, 50% rh) and mild environmental temperature (18°C, 50% rh) exposure on physical performance and soccer-specific decision-making in male football players after completing a 92-min intermittent cycling sprint protocol. The results showed that the decision-making was impaired in the hot compared to the mild temperature condition.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results of the present study showed that exposure to heat led to a decrease in anticipation performance in elite female players. Our results mirror those reported by Donnan et al 2 who examined the effects of hot (32°C, 50% rh) and mild environmental temperature (18°C, 50% rh) exposure on physical performance and soccer-specific decision-making in male football players after completing a 92-min intermittent cycling sprint protocol. The results showed that the decision-making was impaired in the hot compared to the mild temperature condition.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings support previous research, which showed that HR was higher during hot conditions, when compared to mild temperature exposure across all the cycling intermittent sprint protocol. 2 Additionally, the gradual increase of the players' HR across the intermittent exercise protocol suggests that female players were experiencing an increase in their physical exertion levels throughout the protocol, suggesting that the exercise intensity and cardiovascular demands increased progressively, ending with physical stress. 54 Furthermore, the observed differences in average HR between hot and mild temperatures emphasized the influence of environment on cardiac response during exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations